EVALUATION OF HBV DNA LEVELS IN SALIVA IN SUBJECTS WITH DIFFERENT VIREMIA AS WELL AS DURING PEGINTERFERON α-2a THERAPY. - Assya Krasteva; Vladimir E. Panov; Dejan Jelev; Krasimir Antonov; Aneta Ivanova; Zahariy Krastev (Peytchinski Publishing, 2013)
Hepatitis B virus is the most important infectious hazard in dental profession. Vectors of HBV infection are not only blood, but also saliva, nasopharyngeal secretions, crevicular fluid.The aim of the study was to evaluate serum and salivary HBV DNA levels in subjects with chronic infection and dynamics of HBV levels during the first 3 months of peginterferon α-2a therapy to be determined. Nineteen parallel samples were tested for HBV DNA by real-time PCR assay. All nineteen sera were positive for HBV DNA with levels ranging from 494 to 6 300 000 000 cp/ml. HBV DNA was detected in all saliva samples even in patients with very low viremia. HBV DNA levels in serum and saliva were quite similar in cases with serum HBV DNA < 10 000 cp/ml. Patients with viremia higher than 10 000 cp/ml had significantly lower HBV DNA levels in saliva.The presence of HBV DNA in saliva might not be only due to transudation or exudation of fluid containing virus from the general circulation into various body fluids. These facts clearly demonstrate the role of saliva in routes of HBV transmission. Our results confirm the possibility of dentist's particiation in infection transmission and suggests that salivary analysis holds promise as a non-invasive approach to identify biomarkers for diseases.